6.4k views
1 vote
Need help with this question. ​

Need help with this question. ​-example-1

1 Answer

5 votes

We have this equation:


\log(x) + \log(x + 99) = 2

First, combine both logarithms using the multiplication property and simplify the expression.


\log[x(x + 99)] = 2


\log[ {x}^(2) + 99x ] = 2

Now, use the definition of logarithm to transform the equation.


{10}^(2) = {x}^(2) + 99x


{x}^(2) + 99x - 100 = 0

Finally, use the quadratic formula to solve the equation.


x = \frac{ -99 ± \sqrt{ {99}^(2) - 4 * 1 * ( - 100)} }{2 * 1}

With this, we can say that the solution set is:

  • x = 1
  • x = -100

We cannot choose x = -100 as a solution because we cannot have a negative logarithm. The only solution is x = 1.

Need help with this question. ​-example-1
User Adam Tropp
by
4.3k points